The Role of Sharia Economic Law Counseling in Protecting the Rights of Mothers and Children at Posyandu Cempaka 4, Poris Jaya, Tangerang City - Abdul Nasrullah; Mohamad Asrori Mulky (IRDH International Journal of Social Sciences & Humanities, 2025)
Sharia economic law counseling is one of the strategic efforts to enhance public understanding of their rights, particularly the rights of mothers and children. This article discusses the role of Sharia economic law counseling conducted in August 2025 at Posyandu Cempaka 4, Poris Jaya, Tangerang City, in providing education, protection, and empowerment for mothers and children in the community. The community service method employed was a participatory approach through direct counseling, interactive discussions, and continuous mentoring. The results of the program indicate an increase in participants’ understanding of the principles of Sharia economic law, including their rights in the context of family, financial planning, and child protection. Furthermore, the activity fostered awareness of the importance of mothers’ roles in managing family economics in accordance with Sharia principles, as well as protecting children’s rights in education, health, and social welfare. These findings suggest that Sharia economic law counseling not only provides theoretical understanding but also encourages changes in attitudes and practical behaviors within the community. Therefore, such counseling has great potential to empower mothers, improve the quality of child care, and strengthen the sustainable protection of children’s rights. This article concludes that the continuity of counseling programs, government support, and collaboration with relevant institutions are essential factors in reinforcing the protection of mothers’ and children’s rights through Sharia economic law at the local level.